The political use of Philippine forestry statistics in the postwar period - Kummer, David M. (Crime, law and social change, 1994)
This paper demonstrates how Philippine forestry statistics were either ignored or deliberately manipulated from the late 1940s to 1986 when former President Marcos fled the country. The implications for social scientists studying land-use change and related matters in countries where elites have a vested interest in concealing their activities could be substantial.